Zent employee social security system - Maringe, Robert (Midlands State University, 2019)
This research study aims at producing a proposed ZENT Employee Social Security System that delivers an automated employee access to social security credit. The development of this system was driven by the incompetence processing of the long serving social security access system. More so, the proposed ZENT social security system was developed using the modern technology adopted from the object oriented language classes. The benefits of developing such as a statement proved to outstand the related costs. The study advanced to outline the system user manual and document the data mining methods used to develop the proposed system.